(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Despite the precautions taken by most teachers, coaches, and educators, injuries during physical education classes, training sessions, and sports competitions are still rare. In the general structure of childhood injuries, this type ranks fourth after household, street and school injuries.